Increased pancreatic islet mass is accompanied by activation of the insulin receptor substrate-2/serine-threonine kinase pathway and augmented cyclin D(2) protein levels in insulin-resistant rats - Rafacho, Alex; Ribeiro, Daniele Lisboa; Boschero, Antonio Carlos; Taboga, Sebastiao Roberto [UNESP]; Bosqueiro, José Roberto [UNESP] (Wiley-Blackwell, 2008)
It is well known that glucocorticoids induce peripheral insulin resistance in rodents and humans. Here, we investigated the structural and ultrastructural modifications, as well as the proteins involved in beta-cell function and proliferation, in islets from insulin-resistant rats. Adult male Wistar rats were made insulin resistant by daily administration of dexamethasone (DEX; 1mg/kg, i.p.) for five consecutive days, whilst control (CTL) rats received saline alone. Structure analyses showed a marked hypertrophy of DEX islets with an increase of 1.7-fold in islet mass and of 1.6-fold in islet density compared with CTL islets (P < 0.05). Ultrastructural evaluation of islets revealed an increased amount of secreting organelles, such as endoplasmic reticulum and Golgi apparatus in DEX islets. Mitotic figures were observed in DEX islets at structural and ultrastructural levels. Beta-cell proliferation, evaluated at the immunohistochemical level using anti-PCNA (proliferating cell nuclear antigen), showed an increase in pancreatic beta-cell proliferation of 6.4-fold in DEX islets compared with CTL islets (P < 0.0001). Increases in insulin receptor substrate-2 (IRS-2), phosphorylated-serine-threonine kinase AKT (p-AKT), cyclin D(2) and a decrease in retinoblastoma protein (pRb) levels were observed in DEX islets compared with CTL islets (P < 0.05). Therefore, during the development of insulin resistance, the endocrine pancreas adapts itself increasing beta-cell mass and proliferation, resulting in an amelioration of the functions. The potential mechanisms that underlie these events involve the activation of the IRS-2/AKT pathway and activation of the cell cycle, mediated by cyclin D(2). These adaptations permit the maintenance of glycaemia at near-physiological ranges.
Keywords: cell cycle proteins; Glucocorticoid; insulin resistance; pancreatic islet; Structure; Ultrastructure